2015
DOI: 10.4137/nmi.s24385
|View full text |Cite
|
Sign up to set email alerts
|

Choline and Fructooligosaccharide: Non-alcoholic Fatty Liver Disease, Cardiac Fat Deposition, and Oxidative Stress Markers

Abstract: This study investigates the treatment of non-alcoholic fatty liver disease (NAFLD) in rats with choline and fructooligosaccharide (FOS). The healthy control group received standard diet. The other three groups consisted of animals with NAFLD. Group Estr received standard diet; group Echo received standard diet plus choline (3 g/100 g diet); and group Efos received standard diet plus FOS (10 g/100 g diet). Food intake, weight, urinary nitrogen, urinary ammonia, total cholesterol, serum triacylglyceride, liver a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 47 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…For example, CHO administration has been reported to increase the DHA to DPA ratio within phosphatidylcholine and phosphatidylethanolamine pools of plasma 43 , a defect of which is believed to represent a lipidomic signatures of the impaired FA elongation and desaturation metabolism of the fatty liver along with increased (relative to palmitate and absolute) concentrations of the monounsaturated species palmitoleate (16:1 n7) and oleate (18:1 n9) 44 . Furthermore, the presence of CHO in multivitamin supplements containing vitamin E may help to increase the hepatic availability of this vitamin 45 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, CHO administration has been reported to increase the DHA to DPA ratio within phosphatidylcholine and phosphatidylethanolamine pools of plasma 43 , a defect of which is believed to represent a lipidomic signatures of the impaired FA elongation and desaturation metabolism of the fatty liver along with increased (relative to palmitate and absolute) concentrations of the monounsaturated species palmitoleate (16:1 n7) and oleate (18:1 n9) 44 . Furthermore, the presence of CHO in multivitamin supplements containing vitamin E may help to increase the hepatic availability of this vitamin 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal microbiota was also improved. Moreover, it has been reported that FOS reduced liver fat content [ 98 ]. In the animal model of NAFLD, induced by 70% sucrose, treatment of FOS reduced hepatic and cardiac steatosis.…”
Section: Modulation Of Gut Microbiota and Its Metabolitesmentioning
confidence: 99%
“…A lack of choline leads to the accumulation of lipids in the liver (Hensley et al, 2000). As a therapeutic drug it is widely used for treating nonalcoholic fatty liver disease, as well other liver disorders (Borges Haubert et al, 2015). Choline had a preventive effect on oxidative damage in mice (Li et al, 2016).…”
Section: Identification Of Biomarkers and Metabolic Pathways In Drug ...mentioning
confidence: 99%